Analysis of Adverse Events in the Treatment of Patients with Non-Valvular Atrial Fibrillation with Oral Anticoagulants: Data from the "ANTEY" Observational Study - Sergey Yu. Martsevich; Yulia V. Lukina; Natalia P. Kutishenko; Anton R. Kiselev; Oxana M. Drapkina (MDPI AG, 2022)
Rationale. Therapy with oral anticoagulants (OACs) in patients with atrial fibrillation (AF) is based on finding the optimal balance of efficacy and safety of these drugs. Data from observational studies are an additional source of information for the adverse events (AEs) of pharmacotherapy. Objective: To investigate pharmacotherapy AEs with OACs in the "ANTEY" prospective observational study in patients with non-valvular atrial fibrillation (AF). Material and Methods: A total of 201 people were enrolled (83 (41.3%) were women). The age of subjects was 71.1 ± 8.7 years (data presented as mean with standard deviation). The study protocol included two face-to-face visits (contacts V0 and V1) and one follow-up (FU) phone contact which were made with the patient at an interval of 6 months. At V0, all patients were recommended to take one of the non-vitamin K antagonist oral anticoagulants (NOACs); starting from V1, warfarin could have been prescribed or NOAC could have been changed. Information about AEs and OACsadministration was collected at V0, V1, and FU. Results. During 1 year of observation, 15 out of 201 patients refused to take OACs, and 186 initiated the recommended drug. Rivaroxaban was initiated in 93 patients, dabigatran in 46, apixaban in 40, and warfarin in 7 patients. There were 55 AEs, 25 of which were serious (SAEs), including 4 deaths. Of the 30 AEs, there were 18 bleedings: eight (8.6%) occurred with the administration of rivaroxaban; four (8.5%) with dabigatran, three (7.5%) with apixaban, and three (42.9%) with warfarin. Differences in the incidence of bleeding events between NOACs and warfarin are statistically significant (p = 0.025). Any AEs increased the chance of nonadherence to treatment nine-fold: OR = 9.2 (CI95%: 3.6-23.5), p < 0.0001. Conclusions. The most typical and common AEs in real-world clinical practice settings treatment with OACs were bleedings, the incidence of which was approximately 8% to 9% in the treatment with NOACs and was much higher with warfarin, bleedings in the treatment with OACs are statistically significantly associated with nonadherence to the use of these drugs in the future.